2022
DOI: 10.1177/15569845221123796
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Left Atrial Appendage Exclusion in Cardiac Surgery Patients With Elevated CHA2DS2-VASc Score: Results of the Randomized ATLAS Trial

Abstract: Objective: Patients with elevated CHA2DS2-VASc scores are at high risk for atrial fibrillation (AF) and thromboembolic events (TE) after cardiac surgery. Left atrial appendage exclusion (LAAE) is a permanent, continuous approach to stroke prevention in AF, overcoming limitations of oral anticoagulation (OAC). We report ATLAS trial results focused on LAAE technical success and perioperative safety and TE rates with and without LAAE in cardiac surgery patients who developed postoperative AF (POAF). Methods: ATLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…15 Concomitant prophylactic surgical left atrial appendage closure at the time of cardiac surgery has not been shown to reduce the risk of stroke or incidence of POAF in patients without atrial fibrillation. 13 , 19 …”
Section: Comparison Of Existing Guidelinesmentioning
confidence: 99%
“…15 Concomitant prophylactic surgical left atrial appendage closure at the time of cardiac surgery has not been shown to reduce the risk of stroke or incidence of POAF in patients without atrial fibrillation. 13 , 19 …”
Section: Comparison Of Existing Guidelinesmentioning
confidence: 99%
“…The multi-national randomized controlled LAAOS III trial showed that surgical ligation of the LAA with an epicardial clip, in addition to coronary artery bypass grafting (CABG), reduced the risk of ischemic stroke or systemic embolism compared to CABG alone in patients with a history of atrial fibrillation, even with similar rates of postoperative anticoagulation in both groups [17]. The ATLAS feasibility trial also demonstrated that LAAL reduced cerebral thromboembolism risk in patients at high risk for stroke and bleeding compared to no ligation [18]. Furthermore, Gerçek and colleagues showed the long-term durability of these results, with a 4.1% decrease in stroke incidence over five years following LAAL in addition to CABG compared to CABG alone, and a 6.3% stroke incidence reduction in patients with CHA 2 DS 2 -VASc scores > 3 [19].…”
Section: Introductionmentioning
confidence: 99%
“…With the AtriClip Left Atrial Appendage Exclusion Concomitant to Structural Heart Procedures (ATLAS) study, Gerdisch et al have taken an important step toward expanding the LAAO evidence to patients without atrial fibrillation. 5 Key takeaways from ATLAS are as follows:…”
mentioning
confidence: 99%
“…By demonstrating that LAAO using the AtriClip (AtriCure, Inc., Mason, OH, USA) can be performed safely and effectively, the ATLAS investigators set the stage for a trial demonstrating the efficacy of the procedure at reducing ischemic stroke risk in patients without a history of atrial fibrillation at the time of surgery. 5 The ATLAS study focused on patients who developed postoperative atrial fibrillation, but based on overlap of the risk factors for cardiac surgery and atrial fibrillation, it is likely that a significant proportion of the recruited patients will develop atrial fibrillation over time, becoming like LAAOS III patients. For this reason, long-term follow-up will be essential in a trial of LAAO in patients without atrial fibrillation.…”
mentioning
confidence: 99%